Mechanistic and structural studies of KDM‐catalysed demethylation of histone 1 isotype 4 at lysine 26. Issue 19 (14th September 2018) - Walport, Louise J.; Hopkinson, Richard J.; Chowdhury, Rasheduzzaman; Zhang, Yijia; Bonnici, Joanna; Schiller, Rachel; Kawamura, Akane; Schofield, Christopher J.
Abstract : N ‐Methylation of lysyl residues is widely observed on histone proteins. Using isolated enzymes, we report mechanistic and structural studies on histone lysine demethylase (KDM)‐catalysed demethylation of N ε ‐methylated lysine 26 on histone 1 isotype 4 (H1.4). The results reveal that methylated H1.4K26 is a substrate for all members of the KDM4 subfamily and that KDM4A‐catalysed demethylation of H1.4K26me3 peptide is similarly efficient to that of H3K9me3. Crystallographic studies of an H1.4K26me3:KDM4A complex reveal a conserved binding geometry to that of H3K9me3. In the light of the high activity of the KDM4s on this mark, our results suggest JmjC KDM‐catalysed demethylation of H1.4K26 may be as prevalent as demethylation on the H3 tail and warrants further investigation in cells. Abstract :